2023
DOI: 10.7759/cureus.37807
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology and the Treatment of Fractures Due to Electric Scooters: A Comparison of Pediatric and Adult Age Groups

Abstract: Aim: Electric scooters (e-scooters) are widely used as alternative vehicles worldwide. These light vehicles do not need a license to drive, and it is also popular among vehicles under the age of 18 among users in Turkey. This is a new term in the literature since there is an increase in accidents resulting from this overuse. This study aims to reveal the patterns and severity of orthopedic injuries resulting from using an e-scooter, especially in the pediatric population.Patients and methods: Patients who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…It is worth noting that Blomberg et al ( 2019) [15] stand out, reporting in their study that 57.1% of all e-scooter-related injury patients were female. Similar findings were reported by Büyükceran et al (2023) [16], where their study revealed that 50.5% of patients were female, while 49.5% were male.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It is worth noting that Blomberg et al ( 2019) [15] stand out, reporting in their study that 57.1% of all e-scooter-related injury patients were female. Similar findings were reported by Büyükceran et al (2023) [16], where their study revealed that 50.5% of patients were female, while 49.5% were male.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, there were only four pediatric patients (under 18 years of age) with a mean age of 13.8 years (range, 12-15 years). Several studies have specifically delved into the pediatric population concerning e-scooter injuries [13,14,16]. For instance, Cohen et al (2022) [13] noted that children exhibit a higher incidence of fractures and polytrauma related to e-scooters when compared to adults, although they experience fewer facial injuries despite a similar rate of head trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominance of falls (single-user accidents) over collisions (involving 2 or more individuals) with high-speed accidents is a common finding also reported by other studies [18,19,27,34,54,55]. This suggests that e-scooters are mainly a danger to their users and thus the need for stricter regulations about their use, such as wearing helmets or implementing speed limits.…”
supporting
confidence: 59%
“…A recent study from Victoria, Australia, noted that 81% of patients with e-scooter-related injuries who were admitted under orthopaedics required surgery [16]. Internationally, up to 30% of fractures require surgical fixation reflective of a novel mechanism of injury that is associated with increased orthopaedic workload and cost to the healthcare system [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Previous work from Australia has noted that between 12-25% of all ED presentations for e-scooter injuries are admitted to the hospital [5,6,9].…”
Section: Introductionmentioning
confidence: 99%